Efektivitas SNEDDS Kombinasi Fraksi Etil Asetat Daun Cengkodok (Melasthoma malabathricum)-Antibiotik terhadap Bakteri Hasil Isolat dari Pasien Ulkus Diabetik - Sari, Rafika; Apridamayanti, Pratiwi; Pratiwi, Liza (Pharmaceutical Journal of Indonesia, 2022)
Diabetic ulcer is a condition where there are neurological abnormalities and peripheral arterial vascular disease that causes infection, ulceration, and/or damage to the deepest skin tissue on the feet of people with diabetes mellitus (DM). The long duration of wound healing is due to the wrong use of antibiotics for a long time, and bacteria tend to become resistant to antibiotics. Antimicrobial compound fraction of cengkodok combined with gentamicin and ciprofloxacin antibiotics for prevention and reduction of antibiotic resistance in the cause of diabetic ulcers. The drug preparation is in the form of self nanoemulsifiying drug delivery system (SNEDDS), which is the optimum combination of cengkodok leaf fraction with gentamicin and ciprofloxacin antibiotics. The use of SNEDDS in this study is because the SNEDDS made from nanoemulsion formulations has small particle size, large surface absorption, and good dispersion, so that it can be evenly dispersed on the skin and penetrates the skin layer. This study aims to determine the effectiveness of the formulation cengkodok leaf fraction with gentamicin and ciprofloxacin antibiotics against B. cereus and S. aureususing the SNEDDS drug delivery system. The test uses the spotless diffusion method without using paper discs. The results showed that the combination of cengkodok leaf fraction with gentamicin and ciprofloxacin antibiotics had better activity against B. cereus and S. aureus than cengkodok leaf fraction, gentamicin and ciprofloxacin only.